(untitled) (Revista de Estudos da Linguagem, 2024)
This study addresses methodological issues of critical discourse analysis and shows how an analytical multi-level approach we developed can be useful in adding theoretical resources and systematization to its methods. The analytical approach is grounded on the macrostructure of human activity (activity, actions, operations) and appropriates resources from text linguistics and sociolinguistics. We crossed this approach with historical and positioning discourses to identify ways of talking, foregrounded, and concealed meanings and ideologies in the statement of the ex-Prime Minister of the United Kingdom Boris Johnson as delivered to the House of Commons on Ukraine on 24 February 2022. Our results point out he established an agreement with the House through an explanatory statement with the predominance of the use of informing discursive procedures, which corresponded for almost half of his procedures. Most of the time Johnson spoke in the future tense through the intense use of the modal auxiliary verb “will”. These, among other linguistic choices, collaborated to conceal the United States and the North Atlantic Treaty Organization’s roles in the invasion of Ukraine, framing responsibility solely on the president of Russia. In conclusion, we comment on the contributions and limitations of the analytical approach.